Corporeality, hyper-consciousness, and the Anthropocene ecoGothic: slime and ecophobia. - Estok, Simon C. (Neohelicon, 2020)
The centrality of slime to corporeal theory can hardly be overstated, and phobic responses to slime belie both the exceptionalism we claim as our birthright, on the one hand, and the realities of our bodily existence and experiences on the other. Slime threatens and enables our sense of corporeal identity; triggers horror and disgust (as well as playful delight in children and sexual arousal in adults); and sits firmly within an ecophobic understanding of agencies outside of ourselves. Gendered and threatening, slime is oddly ambivalent matter. It is the stuff of which Anthropocene ecoGothic dreams are made, matter well beyond our command that threatens us precisely because of the ineluctability of its agential presence in our lives.